Antioxidant, anti-inflammatory and immunomodulatory activity of chloroform extract of the leaves of Chuquiraga lessing "Huamanpinta" - Ramírez, Emilio (2014)
In the present study were evaluated the antioxidant, anti-inflammatory and immunomodulatory activity of chloroform extract from the leaves of Chuquiraga lessing "huamanpinta" and was performed the identification and structure elucidation of flavonoid secondary metabolites, antioxidant activity was evaluated by the method of difenilpycrilhidrazyl (DPPH) and was measured the activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA). To analize) antiinflammatory activity was used subplantar edema method according Winter; and to immunomodulatory activity the method of speed of clearing of ink. Flavonoids, triterpenes, steroids, alkaloids, tannins, phenolic compounds, sesquiterpene lactones were identified. With UV spectroscopic analysis the following flavonoids were elucidated: 5,6,7-trihidroxi-4’-metoxiflavona; 3’,5,6,7-tetrahidroxi-4’-metoxiflavanona; 4’,5,7,8-tetrahidroxiflavona; 5,7,8-trihidroxi-4’-metoxiflavona. The in vitro antioxidant activity of 86,4% (300 μg/mL) and in vivo increases the activity of antioxidant enzymes CAT (2146,8 IU/mL blood), SOD (10,12 IU/mL blood) and reduces lipid peroxidation as MDA (3,6 μmol/mL blood). Most inflammatory efficiency was 300 mg/kg (39,1%) and immunomodulatory activity was 200 mg/Kg (48,23%). It is concluded that chloroform extract presents antioxidant, anti-inflammatory and immunomodulatory activity.